A comparative evaluation of the inulin utilization potential of two Bifidobacterium animalis subsp. lactis strains for the development of a synbiotic powder - JAMES, LIGIMOL; Puniya, Anil K.; Singh, Kishan (International Journal of Biological Research, 2014)
Assessment of the compatibility between the probiotic and prebiotic is identified as a critical step while developing synbiotic products. So a study was conducted to compare the inulin utilization potential of two Bifidobacterium animalis subsp. lactis strains for selecting a strain for the development of a lyophilized synbiotic product. The growth stimulatory effect of inulin was found to be more prominent on Bifidobacterium animalis subsp. lactis B420 than on Bifidobacterium animalis subsp. lactis Bb-12. So a synbiotic pair of Bifidobacterium animalis subsp. lactis B420 and inulin was selected for the development of the synbiotic product. The developed product had a high probiotic count of  6.5x108 cfu/g, showing a survival rate of 65%. On assessing the probiotic count of the developed product during storage, a marked reduction was observed on room temperature storage with the counts reducing to the level of less than five log cfu/g after 60 days. In contrast the count remained in the range of eight to nine log cfu/g even after 60 days of refrigerated storage. So it could be a suggested that considering the probiotic stability and viability problems pertaining to fermented dairy products, lyophilized products could be potential alternatives as matrices for the delivery of probiotics to humans. Keywords: Bifidobacterium animalis subsp. lactis Bb-12, Bifidobacterium animalis subsp. lactis B420, Inulin, Lyophilized powder, Synbiotics.